Jurisprudential-legal Review of the Validity of the Approvals of the Expediency Council - Seyd Fazlolah Mousavi; Khosro Hoseinpour (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Jurisprudence and expediency are controversial issues that took place after the Islamic Revolution before the jurists and thinkers for practical reasons. In the 1979 constitution, legislation by Parliament was limited to the compatibility with the Islamic law and constitution, and thus the Guardian Council was determined for the maintenance of this state of affairs. In practice, Parliament had passed laws according to the expediency and necessity that were met with Guardian Council opposition, and during this period, there were tensions and impasses in the country. Expediency Council was created after instances of interference with the late leader of the revolution to solve such problems, for his initiative and according to his Command on 6 February 1988.  This entity in the 1989 revision of the constitution has been a legal status.This paper reviews the fundamentals of jurisprudence expediency, the genesis of the Expediency Council, and the most important duty of this council.